Հայ ժողովրդական հավատալիքները Հովհ. Թումանյանի գրական ժառանգության մեջ - Հասմիկ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Литературное наследие Ов. Туманяна является ценным этнографическим источником по традиционным армянским верованиям. Hovh. Toumanyan’s literary legacy is a valuable ethnographic source for studying Armenian traditional beliefs.
Keywords: Literature; Language and Literature; G Geography; Anthropology; Recreation; GR Folklore